Applied pedagogies : strategies for online writing instruction - Ruefman, Daniel, 1983-; Scheg, Abigail G., 1986- (Utah State University Press, 2016)
"Examines the pedagogical practices employed by successful writing instructors in digital classrooms at a variety of institutions, and provides research-grounded approaches to online writing instruction. Provides ways to employ the best instructional strategies possible for today's diverse and dynamic digital writing courses"--Provided by publisher